Zero trust architecture: challenges and recommendations for successful implementation - Yesin, V.I.; Vilihura, V.V.; Uzlov, D.Y. (Radiotekhnika, 2024)
To protect the modern digital enterprise, a new approach is needed today to ensure secure access to your own corporate resources anytime, anywhere, and their efficient operation regardless of where they are located. The traditional perimeter-based network protection model is unable to adapt to the development of modern technologies. Therefore, enterprises have begun to rethink the traditional network security perimeter, leaning toward a new concept and architecture of protection. Such a concept is currently the security paradigm called "zero trust". The zero trust concept attracts special attention of researchers and practitioners, as it is able to meet new requirements for information security and cybersecurity. One of the factors contributing to the demand for zero trust architecture is the increased complexity and heterogeneity of modern IT systems. However, despite the popularization of this concept and the obvious security benefits from its use, there are certain difficulties in its implementation in enterprises. Deploying a zero trust architecture is quite complex from both a technical and organizational point of view. At the same time, interested representatives of enterprises are not yet fully aware of the advantages and disadvantages of the zero trust concept, which significantly hinders its application, which is still in the process of development. The main serious factors hindering the implementation of the zero trust concept are the lack of information for choosing a zero trust solution and the insufficient number of qualified specialists in this area. That is, today there is a problem associated with a certain lack of awareness about the concept and zero trust architecture (about their theoretical and practical significance) for choosing the right solution when building a security system for a corporate information system in modern conditions. This paper aims to solve this problem by summarizing existing research and the experience of various international companies that are implementing this approach in practice. The purpose of this paper is to assist IT enterprise information security professionals in the selection and application of enterprise-relevant, forward-looking zero trust architectures to increase the cybersecurity of the enterprise information system. This paper briefly discusses the conceptual zero trust architecture, its main logical components, deployment models, threats associated with zero trust architecture, and some recommendations for successful implementation of zero trust architecture in the IT enterprise.